DANCE, SONG ACTING MODE AND CHOREOGRAPHY OF SILENT ARTISTS (A STUDY): मूक -बधिर कलाकारों की नृत्य, गीत अभिनय विधा व कोरियोग्राफी(एक अध्ययन) - Singh Naruka Phoolita, Yogendra (International Journal of Research -GRANTHAALAYAH, 2015)
It is difficult for normal artists to dance without music and music, but it is equally comfortable for deaf and dumb artists. Sound and music have no purpose for silent-deaf artists. The artist does not dance to the melody of the music, but rather to the chords of his choreographer. His dance forms are based on the notion of dance without music. A choreographer with a good knowledge of the sign language of the silent and deaf can master it in dance. is. सुर व संगीत के बिना सामान्य कलाकारों के लिए नृत्य करना मुश्किल कार्य है लेकिन मूक-बधिर कलाकारों के लिए यह उतना ही सहज हैं। मूक-बधिर कलाकारों के लिए सुर व संगीत का कोई प्रयोजन नहीं है। यह कलाकार संगीत की किसी तान पर नहीं थिरकते अपितु यह अपने कोरियोग्राफर के ईशारों पर थिरकते है।इनकी नृत्य विधा डान्स विदआऊट म्यूजिक की धारणा पर आधारित होती हैं।मूक-बधिरांे की सांकेतिक भाषा का अच्छा ज्ञान रखने वाला केारियोग्राफर इन्हे नृत्य में पारंगत बना सकता है।